Pemikiran Al-Farabi tentang Pendidikan dan Relevansinya dengan Dunia Kontemporer - Humaedah Humaedah; Mujahidin Almubarak (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2021)
According to Al-Farabi education is a means of obtaining a series of values, knowledge and skills. Islamic education according to Al-Farabi must emphasize the formation of morals and reason. Utilization of reason to acquire knowledge must be accompanied by good character building. The purpose of this writing is to find out the biographical background, life, and thoughts with Islamic education in this modern era. The method used in the preparation of this paper is the library research method. Researchers collected data sources through text literature, both books, journals, and articles related to this discussion. The primary source of this paper is the journal of Educational Concepts According to Al-Ghozali and Al-Farabi (a comparative study of thought) by Agung Setyawan, UIN Sunan Kalijaga. The results showed that Al-Farabi was a philosopher and Muslim scientist who mastered various fields of science and language. The thought of education according to Al-Farabi is to prioritize the formation of morality or morality. Knowledge according to Al-Farabi is clean, and will only be obtained by people with a clean heart and good character. In the educational process according to Al-Farabi a student must pay attention to any differences in the potential that students have.